Vainglory : the forgotten vice - DeYoung, Rebecca Konyndyk (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2014)
Vainglory-- a keen desire for attention and approval. Although contemporary culture has largely forgotten about vainglory, it was on the original list of seven capital vices and is perhaps more dangerous than ever today. DeYoung tells the story of this vice, moving from its ancient origins to its modern expressions. She defines vainglory, gives examples from popular culture, and discusses other vices associated with it such as hypocrisy and boasting. She then explores personal spiritual practices that can help us resist it and community practices that can help us handle glory well.
Glory, goodness, and getting attention -- Varieties of vainglory -- Vainglory's roots: pride and fear -- Honesty required: hypocrisy and habituation -- Making a mockery of magnificent virtue -- Practices of resistance, places of encouragement -- Sharing the (lime)light: -- Grace, formation, and community.
Includes bibliographical references (pages 136-150) and index.
Keywords: Pride and vanity; Deadly sins